Pendampingan Produk Usaha Mikro Kecil dan Menengah (UMKM) Dalam Pengurusan Sertifikasi Halal Melalui Program SEHATI - Shokhikhah, Nur Shaikhut Toharotus; Aprillia, Riska Putri; Sabila, Alfina Rahma; Yulianto, Avif; Janah, Azi Alfi; Anjani, Namira Nurma; Andriani, Andriani (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
Assistance for micro, small, and medium enterprise (MSME) products in obtaining halal certification through the SEHATI program is carried out with the agenda of assistance in obtaining halal certification as an effort to increase consumer confidence and increase market share. Apart from that, there is a program from the SEHATI government for free halal certification, which can provide benefits for business owners in registering halal product management. The approach method used is descriptive qualitative research using field research. This service uses methods of socialization and direct assistance for MSME actors to obtain complete halal certification permits. From the discussion, it is known that there are 30 MSME players who have successfully registered and obtained halal certification for their products.